PERLINDUNGAN HUKUM TERHADAP PEKERJA PARUH WAKTU APABILA TERJADI KECELAKAAN KERJA - Wiwit Triani, Ketut; Putra Ariana, I Gde (Kertha Semaya : Journal Ilmu Hukum, 2013)
Business in Indonesia is increasingly growing. Many companies desire to develop their business to be bigger, so it takes a lot of manpower in form of full time employment, part-time employment, temporary or replacement workers. The workers may experience accident in the implementation of their job. So a paper entitled “Legal Protection for The Part Time Workers When Working’s Accident Occurred” was compiled. By using normative research methods, this paper gives knowledge of legal protection for the part-time workers in case of working accidents and how far the responsibilities held by the company when occupational injuries experienced by part-time workers. The Rights of Part-time workers themselves are not regulated specifically in the law of employment. However, in case of accident takes place the company where part-time works should be responsible in full accordance with the legislation in force, by giving insurance or working accident compensation.
Keywords: Protection, Responsibility, Part Time Worker, Work Accident